Mulberry Hollow [large type] - Hunter, Denise, 1968- (Hunter, Denise, 1968- Riverbend romance, 2022)
"Avery Robinson decided to be a physician after helplessly watching her mother lose a battle with a terrible disease. Now at risk of developing the same illness, Avery guards her heart from love. She's driven to protect her loved ones as a workaholic doctor in the tiny mountain town of Riverbend Gap, North Carolina. Contractor Wes Garrett is hiking the Appalachian trail, in memory of the man who died saving his life, when an illness racks his body. After an agonizing fifteen-mile hike to Avery's clinic, he collapses on her doorstep. He recovers to find himself in debt again, this time to a beautiful doctor. When he decides to help her renovate a rundown carriage house, the obstacles to their attraction sprout like weeds--starting with the woman waiting for Wes at the end of the trail. Will he be able to relinquish the debt he owes his best friend? And will Avery find the courage to risk everything for love? The second book in Denise Hunter's popular Riverbend Romance series explores what it might be like to live fearlessly and free."--